Altered brain activity during active forgetting in highly superior autobiographical memory: Evidence from an item-method directed forgetting - Valerio Santangelo; Tiziana Pedale; Sarah Daviddi; Ilenia Salsano; Simone Macrì; Patrizia Campolongo (iScience)
Summary: Individuals with highly superior autobiographical memory (HSAM) challenge current memory knowledge, yet it remains unclear if their superior memory stems from impaired forgetting. Using a directed forgetting paradigm, we examined this in 12 individuals with HSAM and 30 controls. During fMRI, participants viewed single words followed by “remember” or “forget” instructions. Five minutes later, participants performed a memory recognition task with old (previously studied) and new words. Behaviorally, both groups showed similar forgetting effects, recognizing fewer to-be-forgotten than to-be-remembered words. However, at the neural level, HSAM individuals showed increased activity in the dorsal and ventral frontoparietal regions during initial word presentation, prior to memory instructions. During active forgetting, they also showed increased activity in the anterior and posterior midline regions. These findings suggest that HSAM individuals require additional neural resources for active forgetting to compensate for their enhanced initial processing of stimuli, enabling them to match the forgetting performance of controls.